The Influence of Work-Life Balance with Work Motivation as Mediating Factor on Job Satisfaction A Prediction toward Transition to New Normal Situation - Inayah Alfatihah; Antonius Soelistyo Nugroho; Elmarian Haessel; Anita Maharani (The Management Journal of Binaniaga, 2021)
This study aimed to examine the effect of work-life balance and work motivation on job satisfaction. The literature review used to discuss the dynamics between variables is work-life balance, motivation and job satisfaction. The approach to this research is quantitative, and the number of respondents involved in this study was 212 people who filled out the survey through an online survey. We collect data during new normal situations. The data analysis technique in this study refers to the structural equation model. The results obtained show that all hypotheses are proven. In other words, this study has shown that work-life balance affects job satisfaction, then work motivation affects job satisfaction, and work-life balance can mediate work motivation on job satisfaction.